The 3' untranslated region of tumor necrosis factor alpha mRNA is a target of the mRNA-stabilizing factor HuR. - Dean, J; Wait, R; Mahtani, K; Sully, G; Clark, A; Saklatvala, J (2001)
Posttranscriptional regulation is important for tumor necrosis factor alpha (TNF-alpha) expression in monocytes and macrophages, and an AU-rich element (ARE) in the 3' untranslated region (UTR) of TNF-alpha mRNA is implicated in control of its translation and mRNA stability. Regulation of mRNA turnover is thought to be mediated by trans-acting proteins, which bind the ARE and stabilize or destabilize the transcript. However, with the exception of the destabilizing factor tristetraprolin, the identity and function of the proteins binding the TNF-alpha mRNA ARE have not been established. To identify other proteins involved in the posttranscriptional control of TNF-alpha, the subcellular location of TNF-alpha mRNA was determined in the macrophage-like cell line RAW 264.7. TNF-alpha mRNA was located in the pellet following centrifugation of cytoplasm at 100,000 x g (P100 fraction). This fraction also contained proteins which formed two distinct ARE-specific complexes with the TNF-alpha mRNA 3' UTR in electrophoretic mobility shift assays (EMSAs). A protein present in these two complexes was purified and identified by peptide mass mapping and tandem mass spectrometry as HuR. In EMSAs both complexes were supershifted by an anti-HuR antibody, while Western blotting also demonstrated the presence of HuR in the P100 extract. A HeLa cell tetracycline-regulated reporter system was used to determine the effect of HuR on mRNA stability. In this system, overexpression of HuR resulted in stabilization of an otherwise unstable reporter-mRNA containing the TNF-alpha ARE. These results demonstrate that the TNF-alpha ARE is a target of the mRNA-stabilizing factor HuR.